Optimization and characterization of quercetin to enhance seedling vigour in greengram (Vigna radiata) under abiotic stress conditions - M, PAVITHRA; MANONMANI, V; MALARKODI, K; UMA, D; KAVITHA, P S (The Indian Journal of Agricultural Sciences, 2024)
A field experiment was conducted during the zaid seasons of 2022–23 and 2023–24 at Tamil Nadu Agricultural University, Coimbatore, Tamil Nadu to study the effect of guava (Psidium guajava L.) leaf extract-treated greengram [Vigna radiata (L.) Wilczek] seeds under abiotic stress. The active ingredient, quercetin, was confirmed using High Performance Thin Layer Chromatography (HPTLC) with a peak area of 0.00039. The experiment was laid out in a split plot design (SPD) comprised of 3 treatments, viz. control (T0); Seeds coated with organic flax seed polymer (T1); Seeds coated with organic flax seed polymer + quercetin @1% (T2) with six replications. Subplots had different irrigation schedules, including weekly irrigation (control) (S0) and withholding irrigation for 15 days at different growth stages [25 DAS (days after sowing) (S1); 35 DAS (S2); 45 DAS (S3)]. Soxhlet-extracted guava leaves resulted in the highest seedling vigour, with 94% germination, 16.9 cm root length, 18.5 cm shoot length, 0.311 g/10 seedlings, and a vigour index of 3299 at 1% concentration. Under moisture stress (PEG 6000-0.2 MPa), quercetin @1% improved germination (62%), root length (13.7 cm), shoot length (15.3 cm), dry matter production (0.170 g/10 seedlings), and vigour index (1750). Enzyme activities, including peroxidase (0.165 U/mg protein/min) and superoxide dismutase (1.127 U/mg protein/min) were highest in this treatment. Significant increases in proline content were observed, ranging from 135–146 mg/g and 137–152 mg/g across both the seasons. Yield/plant increased to 16.7 g (4.4 kg/plot) in season 1 and 17.3 g (4.6 kg/plot) in season 2. Thus, quercetin @1%, infused in flax seed, effectively mitigates drought stress, offering a sustainable solution for organic cultivation.